2003
DOI: 10.1021/bi026944d
|View full text |Cite
|
Sign up to set email alerts
|

Distal Site Aspartate Is Essential in the Catalase Activity of Catalase-Peroxidases

Abstract: Structural and biochemical characterization of aspartate 152 at the distal heme side of catalase-peroxidase (KatG) from Synechocystis PCC 6803 reveals an important functional role for this residue. In the wild-type protein, the side chain carboxyl group of Asp152 is 7.8 A apart from the heme iron and is hydrogen-bonded to two water molecules and a KatG-specific large loop. We have prepared the site-specific variants Asp152Asn, Asp152Ser, Asp152Trp, and Pro151Ala. Exchange of Asp152 exhibited dramatic consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 26 publications
3
77
0
Order By: Relevance
“…64; www.pymol.org). Asp-137, and even the oxyferryl group in the same manner as suggested for hydrogen peroxide in the catalatic reaction (61). Transformation of diazene to hydrazine and ammonia (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…64; www.pymol.org). Asp-137, and even the oxyferryl group in the same manner as suggested for hydrogen peroxide in the catalatic reaction (61). Transformation of diazene to hydrazine and ammonia (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Very similar results within experimental error were obtained with MtbKatG (10 lM) and BLC (10 lM). In any case, two peaks of equal areas for 18 The pH profiles of catalatic activity for KatGs are quite different from those for monofunctional catalases. The latter's catalatic activities are essentially pH-independent from pH 5 to 10 [20], whereas KatGs show a sharp optimum between pH 6 and 7 [9].…”
Section: Resultsmentioning
confidence: 86%
“…Another important residue at the distal heme cavity is D152, which is part of the substrate channel and has its side chain carboxyl group pointing toward the heme pocket. It participates in maintaining a rigid and extended hydrogen-bond network, which is important for the H 2 O 2 oxidation reaction [18,24]. Variants that had these residues exchanged (D152S, W122F, Y249F, and R439A) showed a significantly reduced catalase (see Table 1) but a normal or even enhanced peroxidase activity [9].…”
Section: Resultsmentioning
confidence: 99%
“…The covalent adduct has been shown to be generated by autocatalytic process (Ghiladi et al, 2005a). Crystallographic analysis of KatG from Bulkhorderia pseudomallei (Bp) has indicated that the side-chain of R409 (corresponding to HmKatG numbering) shows conformational change depending on both of pH and the physicochemical state of the active site (Carpena et al, 2005 M244L] in BpKatG considerably decreased the catalase activity, whereas the peroxidase activity was even enhanced (Regelsberger et al, 2000;Jakopitsch et al, 2004;Singh et al, 2004 Y218F] in the M244-Y218-W95 covalent adducts induced complete loss of the catalase activity, whereas the peroxidase activity was highly enhanced in Sy KatG (Jakopitsch et al, 2003a;Jakopitsch,et al, 2003b). M244 in the adduct also has any significant role in the enzyme, whereas the substitution of Met to Ile considerably attenuated the catalase activity but did not lose at all, and enhanced the peroxidase activity Singh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%